Introduction to healthcare for Turkish-speaking interpreters and translators - Crezee, Ineke; Eser, Oktay; Karakaş, Fatih (John Benjamins Publishing Company, 2022)
"Health interpreters and translators often face unpredictable assignments in the multifaceted healthcare setting. This book is based on the very popular international publication (Crezee, 2013) and has been supplemented with commonly asked questions and glossaries in Turkish. Turkish is the home language of a very significant number of (now often elderly) migrants in countries outside of Turkey and provides an invaluable resource to those interpreting for these migrants in the healthcare setting. The book will also be invaluable to those interpreting for medical tourists from Turkey travelling to other countries for treatment. In short, this is an exceptionally useful and easily accessible handbook, in particular for interpreters, translators, educators, cultural mediators, health professionals and other practitioners working between Turkish and English - or other languages. Speakers of Turkish represent a rich and diverse range of historical, religious and cultural traditions. This book covers some of those, while also describing the Turkish healthcare system and touching on cultural beliefs and traditional approaches to health. This unique books is an indispensable vade mecum ("go with me") for anyone wishing to navigate language access involving speakers of Turkish in the healthcare setting"--